"You Have Not Sought the Lost":1 A Reflection from Europe on the WCC Theme. (11th April 2013) - Cruchley‐Jones, Peter
Abstract This article queries the title "God of Life, " and wonders how this can be intelligible in a European context where God is not associated with life, nor is seen to bring anyone closer to justice or peace. Having outlined the conflicted context of Europe for faith, this article goes on to explore if this context might, nevertheless, offer any clues to constructing a mission theology for the God of Life. Using the parable of the prodigal son, the article begins to explore themes of lostness that subvert the typical reading of this parable and open out an alternative perspective on the experience of God as absent. This creates a fresh space in which it might be possible for the God of Life to come in new guises, bringing fresh companions inviting us to enter into a new spirit of mission.